Keamanan Internet Untuk Anak Dibawah Usia 17 Tahun - Muhammad Azwin Rifai; Reggya Ahmad Armansyah; Muhammad Riza Hashbillah (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Internet security for children under the age of 17 has become an increasingly important issue in line with the rapid development of digital technology. This research aims to identify the risks faced by children when accessing the internet and to explore solutions that can be implemented to protect them from online threats. The method used in this research is the Quantitative Descriptive Research Method with Questionnaire Surveys and Literature Studies, focusing on the analysis of internet dangers, understanding of internet safety, and the roles of parents, educators, and related parties in protecting children in the online world. The research results show that despite various measures being implemented and the level of understanding of internet safety among children and teenagers in this study, there are still many issues in ensuring the safety of children when they use the internet. This research suggests the development of artificial intelligence (AI)-based technology to monitor children's online activities, raising awareness among parents and educators about the importance of supervision, and the need for stricter government policies. With the collaboration of various parties, it is hoped that a safer digital environment for children will be created.